Diet-induced weight loss and markers of endothelial dysfunction and inflammation in treated patients with type 2 diabetes. (October 2016) - Berk, K.A.; Oudshoorn, T.P.; Verhoeven, A.J.M.; Mulder, M.T.; Roks, A.J.M.; Dik, W.A.; Timman, R.; Sijbrands, E.J.G.
Summary: Background & aims: Overweight and obesity increase cardiovascular mortality in patients with type 2 diabetes (T2D). In a recent trial, however, diet-induced weight loss did not reduce the cardiovascular risk of patients with T2D, possibly due to the parallel intensive medical treatment. We investigated the effect of diet-induced weight loss on cardiovascular risk factors in overweight and obese patients with T2D, and whether this effect was influenced by the use of statins, ACE inhibitors, metformin and duration of T2D. Methods: Patients with T2D and BMI >27 were subjected to an energy-restricted diet during 4 months. Before and after intervention, plasma levels of sICAM-1, sVCAM-1, hsCRP, vWF and classical biomarkers were measured. The association of the change in biomarker levels with medication use and T2D history, corrected for age, sex and change in insulin dose, was tested by matched linear regression analyses. Results: In 131 patients, the diet resulted in weight loss of 10.2 kg (95%CI 9.2, 11.3; p  < 0.001), improved median levels of HbA1c (−7.0 mmol/mol (95%CI −8.5,  −5.0); p < 0.001), LDL cholesterol (−0.2 mmol/L (95%CI −0.4,  −0.1); p < 0.001), sICAM-1 (−22.4 ng/mL (95%CI −37.1,  −8.7); p = 0.001), vWF (−3.9 IU/mL (95%CI −6.4,  −1.4); p = 0.003) and hs-CRP (−0.6 mg/L (95%CI −1.2,  −0.2); p = 0.007), but did not affect sVCAM-1 levels (1.6 ng/mL (95%CI −41.5, 48.6); p = 0.949). Duration of T2D and medical treatment were not associated with these effects, except for an association between statin use and change in sVCAM-1, where statin users improved more. Conclusion: Diet-induced weight loss reduced the levels of biomarkers of endothelial dysfunction and inflammation in overweight and obese patients with T2D independently of medication use and T2D duration. Even on intensive medical drug treatment as well as after a long history of T2D, patients may still profit from diet-induced weight reduction.